Engineering Bipolar Doping in a Janus Dual-Atom Catalyst for Photo-Enhanced Rechargeable Zn-Air Battery - Ning Liu; Yinwu Li; Wencai Liu; Zhanhao Liang; Bin Liao; Fang Yang; Ming Zhao; Bo Yan; Xuchun Gui; Hong Bin Yang; Dingshan Yu; Zhiping Zeng; et al. (Nano-Micro Letters)
Highlights Janus dual-atom catalyst (JDAC) with bifunctional centers was synthesized via a single-step bipolar doping strategy to promote efficient charge separation and superior electrocatalytic performance. The in situ X-ray absorption near-edge structure and Raman spectroscopy analyses demonstrated that Ni and Fe centers in JDAC function as effective sites for oxygen evolution reaction and oxygen reduction reaction, and effectively suppress photoelectron recombination while enhancing photocurrent generation. The assembled JDAC-based light-assisted rechargeable zinc–air batteries exhibited extraordinary stability at large current densities (300 cycles at 50 mA cm−2, and 6000 cycles at 10 mA cm−2 under light illumination).